2020
DOI: 10.1161/circulationaha.119.044924
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Trajectories of Cardiac Allograft Vasculopathy After Heart Transplantation

Abstract: Background: Cardiac allograft vasculopathy (CAV) is a major contributor of heart transplant recipient mortality. Little is known about the prototypes of CAV trajectories at the population level. We aimed to identify the different evolutionary profiles of CAV and to determine the respective contribution of immune and nonimmune factors in CAV development. Methods: Heart transplant recipients were from 4 academic centers (Pitié-Salpêtrière and Georges Pomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…Immune activation events in the early post‐transplant course are known risk factors for CAV development. Recently, ACR ≥2R and class II DSA during the first post‐transplant year have been identified as independent predictors of CAV trajectories 42 . Consequently, serial early assessments of ddcf‐DNA possibly reflecting these immune activation events could be useful to further inform about an individual’s risk of CAV later in the post‐transplant course pending future longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Immune activation events in the early post‐transplant course are known risk factors for CAV development. Recently, ACR ≥2R and class II DSA during the first post‐transplant year have been identified as independent predictors of CAV trajectories 42 . Consequently, serial early assessments of ddcf‐DNA possibly reflecting these immune activation events could be useful to further inform about an individual’s risk of CAV later in the post‐transplant course pending future longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 Their findings also suggest that proliferation signal inhibitors such as sirolimus have a greater impact in reducing the risk of CAV irrespective of LDL-C levels. In contrast, a large multicentre observational analysis by Loupy et al recently suggested an association between a 1-year LDL-C cut off ≥1.0 g/L (2.6 mmol/L) and risk of CAV progression 21 . We evaluated LDL-C at 1-year post HT as a continuous variable to better characterize the association with angiographic CAV as well as earlier signs of CAV using IVUS data.…”
Section: Discussionmentioning
confidence: 89%
“…Binary univariate regression was performed in advance, and parameters associated with class membership with p < 0.05 were included in multivariable multinominal logistic regression models. The NIHSS was used in categories of no (0), mild (1-4), moderate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), moderate to severe (16)(17)(18)(19)(20)(21) and severe (22-42) symptoms.…”
Section: Multinominal Regressionmentioning
confidence: 99%
“…To this end, a systematic assessment of patient reported outcomes measures (PROMs) has been shown to deliver information beyond routine examinations by physicians and to identify disabling deficits in every-day life after stroke [17,18]. A possible strategy towards understanding the development of different outcomes and towards risk stratification is classifying patients by the results of their outcomes and analyzing class characteristics, as shown for diabetes [24] and heart transplantation [20]. In mild to moderately affected stroke patients from an outpatient setting, a retrospective analysis showed promising results building distinct profiles or classes using the Patient-reported Outcomes Measurement Information System (PROMIS) [16].…”
Section: Introductionmentioning
confidence: 99%